2016
DOI: 10.1093/ijnp/pyw027
|View full text |Cite
|
Sign up to set email alerts
|

Serum Cytokine Profiles of Children with Obsessive-Compulsive Disorder Shows the Evidence of Autoimmunity

Abstract: Background:Previous reports have described an association between autoimmunity and primary obsessive compulsive disorder. This study aimed to investigate any differences in the levels of T helper 1, 2, and 17 effector cell cytokines between obsessive compulsive disorder patients and the control group.Methods:The study included 34 children (23 males, 11 females), aged between 7 and 17 years, with a diagnosis of obsessive compulsive disorder prior to receiving treatment. The control group consisted of age- and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 56 publications
1
20
3
Order By: Relevance
“…Further studies [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ] were carried out enabling a meta-analysis [ 31 ] ( Table 1 ), which found decreased IL-1β levels and decreased TNFα (tumor necrosis factor α) levels in non-depressed OCD patients (but not in OCD patients with possible comorbid depression), and increased IL-6 levels in adult medication-free OCD patients (but not in OCD children with possible medication use) compared to controls. More recently, discrepancies were found with this previous meta-analysis concerning TNF-α with increased levels in OCD patients [ 32 , 33 , 34 ] ( Table 1 ). Despite these discrepancies, the increased IL-6 levels seem a consistent result as they were replicated in a recent study [ 34 , 35 ] ( Table 1 ).…”
Section: Immunological Changes In Ocdcontrasting
confidence: 60%
“…Further studies [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ] were carried out enabling a meta-analysis [ 31 ] ( Table 1 ), which found decreased IL-1β levels and decreased TNFα (tumor necrosis factor α) levels in non-depressed OCD patients (but not in OCD patients with possible comorbid depression), and increased IL-6 levels in adult medication-free OCD patients (but not in OCD children with possible medication use) compared to controls. More recently, discrepancies were found with this previous meta-analysis concerning TNF-α with increased levels in OCD patients [ 32 , 33 , 34 ] ( Table 1 ). Despite these discrepancies, the increased IL-6 levels seem a consistent result as they were replicated in a recent study [ 34 , 35 ] ( Table 1 ).…”
Section: Immunological Changes In Ocdcontrasting
confidence: 60%
“…66,67 The only study evaluating primary pediatric OCD reported increased levels of IL-17A (P = .03), TNF-alpha (P = .01), and IL-2 (P = 0.02) in patients with OCD than in controls; symptom severity and illness duration were not significantly correlated with cytokine levels. 68 This may be further supported by the finding in patients with earlyonset OCD revealing increased production of inflammatory cytokines by monocytes when stimulated with lipopolysaccharide (LPS) or dexamethasone and LPS. 69 As such, patients with OCD may possess an intrinsic vulnerability to monocyte activation, which may generate an increased inflam-matory response.…”
Section: Immune Dysregulationmentioning
confidence: 83%
“…Studies have shown that variation in the TNFRSF1A gene can contribute to the progression of MS [72]. Simsek et al suggested that low levels of TNFα through the TNFRSF1A may cause OCD or worsen it [73]. Although further studies on the changes in this gene in OCD can be valuable.…”
Section: Discussionmentioning
confidence: 99%